On controlling preload and estimating anti-loosening performance in threaded fasteners based on accurate contact modeling. (March 2016) - Zhu, Linbo; Hong, Jun; Jiang, Xiangjun
Abstract: This paper proposed torque–preload formulas to control preload and estimate anti-loosening performance in threaded fasteners based on accurate contact modeling. To avoid the error introduced by assumptions about traditional contact pressure, the contact modeling on underhead and thread surfaces was treated as punch problems for getting the actual contact pressure. Three different coordinate systems were applied to characterize the change history of the direction of friction forces, and symbol integration was then utilized to conduct the torque–preload relationship. The influences of main parameters on torque–preload relationship under tightening and loosening were discussed. Experimental verification was also conducted showing that the suggested approach is a better choice to precisely control preload and estimate anti-loosening performance in threaded fasteners. Highlights: Accurate torque–preload formulas are represented by contact modeling and surface integration. Contact pressure distribution of underhead and thread surfaces can be quantitative rather than assumptions. Friction torque calculation involving fastener geometry is more accurate.